Penggunaan dan Penerapan Metode Pengukuran Energi dalam Upaya Penghematan Energi di Galeri Ciumbuleuit Hotel dan Apartemen Bandung - delfiyanti, delfiyanti (Jurnal Daya Saing, 2016)
The new index building energy performance that can allow management to follow the energy consumption for months. There are many variables that change over time during the normal routine of the day. Based on the analysis performed, the authors conclude beberpa energy management research results Galeri Ciumbuleuit Hotel and Apartment, associated with facilities and energy consumption. Initial audit methods and a detailed audit which is used for energy savings can process data over the last 3 years, and can be applied. Dibangunan energy audit method can be used to suppress the use of potential energy savings, thus saving efforts can be done better and more useful. Keywords: Method of Measurement of Energy, Energy Saving